CIPP MODEL APPROACH IN EVALUATING VACCINE MONITORING IMPLEMENTATION AT X PUBLIC HEALTH CENTER - Rudy Chendra; Lutfhiana Nabella; Indah Pasha Palingga; M. Yoga Jusri Pratama; M. Defri Adi Shah Putra (RADJA PUBLIKA, 2026)
This study aims to evaluate the implementation of the Electronic Logistics Immunization Monitoring System (SMILE) at the X Community Health Center using the Context, Input, Process, Product (CIPP) model. This research method is qualitative with a descriptive approach. There were 9 informants and data were obtained through in-depth interviews, observations, and document reviews, then analyzed using thematic analysis methods. Based on the results of the context aspect of the study, program needs have been adjusted to a region-based approach to facilitate monitoring of immunization targets, although there are still obstacles in certain target groups. Human resources and infrastructure input are available, but limitations in technical capabilities of officers, double workloads, and internet and electricity connections. The implementation process is in accordance with the SOP, but there are delays in data input due to double recording. The SMILE product has a positive impact on vaccine logistics management and facilitates monitoring of vaccine distribution. Thus, the implementation of the SMILE program at the X Community Health Center has been running quite well, but still requires improving the capabilities of officers, strengthening the network, and optimizing the reporting system to increase program effectiveness.